Neutron elastic scattering cross-section measurements at 175 MeV - M. Tesinsky (2018)
An off-line data analysis of an experimental campaign on elastic neutron cross-section measurements at 175 MeV for iron and bismuth performed by the scandal set-up has started. Energy calibration has shown expected values of energy resolution and MCNPX simulations have provided suggestions for further analysis.